Letter to Editor Didactic and Certified Trauma and Acute Care Surgery Fellowship is Inevitable Demand of Pakistan - Saqib, Sabah Uddin (Pakistan Armed Forces Medical Journal, 2021)
Discussions about the content and competencies of any postgraduate training program mainly focus on what the graduates need in long run after completion of training1. However, from the prospect of any progressive country, a post-graduate training program should also liaise with the demands of the country. Over the past decade, the acute care surgery practice paradigm has become a defined entity in the developed world and didactic fellowship training programs in trauma and acute surgery have been implemented. In recent years, the American Association for Surgery has matured to 20 different disciplines of trauma and acute care2.